Communication in mathematics: the role of language and its consequences for English as second language students - Khalid, Madihah; Tengah, Mohd Khairul Amilin (2007)
This paper will look at the emphasis on communication in the new Brunei mathematics curriculum for primary schools, the components of mathematics communication to be developed and the approaches to develop communication among Bruneian students as stated and suggested in the new curriculum document. This paper will also present problems pertaining to Bruneian students in terms of communicating using a second language because mathematics is taught in English in Brunei while most of the students are second language users of English.